The Effect Of Green Accounting, Environmental Performance, And Company Size On Profitability In Manufacturing Companies In 2020–2024 - Oktaviana, Vika Kinanti; Darmawati, Sri Sapto (Universitas Gunadarma, 2025)
This study aims to analyze and explain the influence of Green Accounting, Environmental Performance, and Company Size on Profitability in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The background of this research departs from the increasing global attention to environmental and business sustainability issues, which requires companies to not only focus on financial aspects, but also pay attention to the environmental impact of their operational activities. This research method uses a quantitative approach with multiple linear regression analysis techniques. Data was obtained from the company's annual report and sustainability report which were the research samples. The Results in the study claim that green accounting and corporate size have negative influence on return on assets (roa). Whereas environmental performance has a positive influence on company's pro capabilities ratio (roa). In the study it claims that green accounting variables, environmental costs, and corporate size are jointly affected by corporate profitability.